A case about the U.S. federal arrangement - Santos, Rodrigo dos (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2012)
Within the federal tax and budgetary debate in Brazil, this article seeks to characterize and conceptualize the federalism as well as the ideal type from the U.S. federal arrangement. Through historical analysis and the crossing of different concepts in the literature about federalism, we observe that there was an evolutionary profile of U.S federalism. The federative model has three general characteristics of forms in its evolution history, they are: i) The competition that is hegemonic at the time of creation of the federal arrangement. ii) The militarism moment that is the transition with centralized power in the federal government. iii) The financial and tax transfers as an element of public policy nationalization. We concluded that the U.S. federal arrangement is an important reference tool for the reduction of regional differences in Brazilian federal arrangement.